U.S. Labor Force Trends. - Lee, Marlene A.; Mather, Mark (Population Bulletin, 2008)
Over the last 40 years, the make-up of the U.S. labor force has been heavily influenced by changing labor markets, globalization, and industrial restructuring. These factors could also influence other features of the work force. Increased mobility of goods, labor, and capital associated with globalization could affect wages. Industrial restructuring affects how workers are spread across industries, occupations, and geographic regions. Moreover, a fall in union membership and a decline in the value of the minimum wage have affected worker access to health care and other employee benefits, and the demand for higher-educated workers together with technological improvements will continue to widen the income gap between the highly educated and the less skilled.